Low-Grade Endometrial Stromal Sarcoma with Intravenous and Intracardiac Extension: A Multidisciplinary Approach. (27th April 2016) - Kudaka, Wataru; Inafuku, Hitoshi; Iraha, Yuko; Nakamoto, Tomoko; Taira, Yusuke; Taira, Rie; Kamiya, Hisashi; Tsubakimoto, Maho; Totsuka, Yuichi; Kuniyoshi, Yukio; Tamaki, Tomoko; Aoyama, Hajime; et al.
Abstract : Background . A rare case of low-grade endometrial stromal sarcoma (LG-ESS) extending to inferior vena cava (IVC) and cardiac chambers. Case Report . A 40-year-old woman had IVC tumor, which was incidentally detected by abdominal ultrasonography during a routine medical checkup. CT scan revealed a tumor in IVC, right iliac and ovarian veins, which was derived from the uterus and extended into the right atrium and ventricle. The operation was performed, the heart and IVC were exposed, and cardiopulmonary bypass was initiated. A right atriotomy was performed, and the intracardiac mass was removed. Then the tumor in IVC and the right internal iliac vein were removed after longitudinal venotomies in the suprarenal and infrarenal vena cava, the right common iliac vein. Next the pelvis was explored. Tumors were found originating from the posterior wall of the uterus and continuing into both the right uterine and ovarian vein. The patient underwent total hysterectomy with bilateral salpingooophorectomy. Complete tumor resection was achieved. Histopathological analysis confirmed a diagnosis of LG-ESS. She showed no evidence of disease for 2 years and 3 months. Conclusions . Our case highlights the importance of a multidisciplinary approach in treating this rare cardiovascular pathological condition through preoperative assessment to final operation.